Development of a Promising Fish Model (Oryzias melastigma) for Assessing Multiple Responses to Stresses in the Marine Environment. (3rd March 2014) - Dong, Sijun; Kang, Mei; Wu, Xinlong; Ye, Ting
Abstract : With the increasing number of contaminants in the marine environment, various experimental organisms have been "taken into labs" by investigators to find the most suitable environmentally relevant models for toxicity testing. The marine medaka, Oryzias melastigma, has a number of advantages that make it a prime candidate for these tests. Recently, many studies have been conducted on marine medaka, especially in terms of their physiological, biochemical, and molecular responses after exposure to contaminants and other environmental stressors. This review provides a literature survey highlighting the steady increase of ecotoxicological research on marine medaka, summarizes the advantages of using O. melastigma as a tool for toxicological research, and promotes the utilization of this organism in future studies.